Perceptions on the Importance, Adoptability, and Extent of Integration of Sustainable Agriculture in Extension Programs in Oriental Negros, Philippines - Cubelo, Jose Edwin C. (Silliman Journal, 2023)
The study describes the agricultural technicians' (ATs) views on the im-portance, practicability, and adoptability of sustainable agriculture (SA), and the extent of its integration into agricultural extension programs in the province of Oriental Negros, Philippines. The study employed a de-scriptive survey design, using Likert-type scales. Respondents to the study include 126 ATs of the Local Government Units (LGUs) of the province. Research findings show that the responding ATs believe in the importance of extension programs that promote SA. They emphasized that for SA prac-tices to be adoptable, these need to be profitable and economically vi-able. However, they also expressed apprehensions about SA's workability and practicability in farms, especially in relation to farmers' capability to make informed decisions about its adoption. SA principles and practices have gained inroads into local agricultural extension programs as mani-fested by the perceived high level of integration of SA topics in agricul-tural extension activities. Among other SA practices, crganic farming, and integrated pest management (1PM) were reported to be highly integrated into agricultural extension programs in the province.